Pertuzumab study in the neoadjuvant setting for HER2‐positive nonmetastatic breast cancer in Australia (PeRSIA). Issue 2 (25th August 2022) - Lok, Sheau Wen; De Boer, Richard; Baron‐Hay, Sally; Button, Peter; Devitt, Bianca; Forster, Benjamin C.; Fox, Peter; Harold, Michael; Ketheeswaran, Sahisha; Kichenadasse, Ganessan; Kiely, Belinda E.; Marx, Gavin; et al.
Abstract: The pertuzumab study in the neoadjuvant setting for HER2+ nonmetastatic breast cancer in Australia (PeRSIA—ML39622) is an analysis of safety and effectiveness data from the pertuzumab patient registry. Although the prognosis of patients with early stage HER2+ breast cancer has been greatly improved by advances in chemotherapy approximately 25% to 30% of patients develop recurrent disease. Our study aimed to examine the effectiveness of neoadjuvant pertuzumab on surgical outcomes, describe the medium‐term effectiveness outcomes of patients treated with pertuzumab, and describe the planned and actual anticancer treatment regimens that patients received. Deidentified data were collected from the patients' medical records and entered into REDCap, between March 2018 and July 2019 (n = 95). The adverse events (AEs) reported most frequently were diarrhea (20; 21.1%), rash (4; 4.2%), and LVSD (4; 4.2%; two patients during neoadjuvant treatment and two patients during adjuvant treatment). AEs, ≥Grade 3 were diarrhea (2; 2.1%) and LVSD (1; 1.1%). Following surgery, a breast pathological complete response (bpCR) was achieved in 65 patients (70.7%; 95% CI: 60.2%‐79.7%) and total pathological complete response (tpCR) in 59 patients (64.1%; 95% CI: 53.4%‐73.9%). All patients who did not achieve a tpCR obtained a partial response (33/92, 35.9%). Our study is the first to capture real‐world data on the use of pertuzumab in the neoadjuvant setting in Australia. The effectiveness and safety data are consistent with those reported in clinical trials of pertuzumab in patients with HER2+ breast cancer, with no new safety concerns. Abstract : What's new? In Australia, the drug approval of the HER2‐directed monoclonal antibody pertuzumab for nonmetastatic HER2+ breast cancer was conditional upon the setting‐up of a national patient registry to capture the medium to long‐term safety and effectiveness outcomes in patients receiving neoadjuvant pertuzumab. Based on the pertuzumab patient registry, this multicenter, prospective, observational study is the first to analyze real‐world data on the use of pertuzumab in the neoadjuvant setting in Australia. The effectiveness and safety data are consistent with those reported in clinical trials of pertuzumab in patients with HER2+ breast cancer, with no new safety concerns.